Hungarian Monitoring, 3 April 1989 . [Magyar rádiófigyelő], 1989. április 3 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev's first official friendly visit to Havana Domestic Affairs: - Good wishes from Soviet leaders on April 4 - Judit Csehák's radio and TV ceremonial speech on events 44 years ago and today's tasks - "We are approaching the point at which our debt becomes unmanageable" - Party general secretary Károly Grósz at a ceremony in Zahony - Károly Grósz's visit to Uzhgorod - László Paskai celebrates mass in Matthias church in honor of Queen Zita who died at the age of 87; Otto Habsburg talks about his mother in a brief interview - Protesters at Nagymaros dam site demand resignation of minister László Maróthy and the government - More groups get involved in researching the site of Petőfi's grave Economy: - "Hungary's economic situation is truly difficult, but it would be mistaken to call it a crisis" says director of East-West Economics Institute in New York Külpolitika: - Gorbacsov első hivatalos, baráti látogatása Havannában Belpolitika: - Szovjet vezetők jókívánsága április 4-e alkalmából - Csehák Judit rádiós és televíziós ünnepi beszéde a 44 évvel ezelőtti eseményekről és a mai feladatokról - Közel vagyunk ahhoz a határhoz, amikor már az adósságtömeg kezelhetetlenné válik" - Mondta Grósz Károly egy záhonyi ünnepségen - Grósz Károly ungvári látogatása - Paskai László celebrálásával ünnepi mise volt a Mátyás templomban a 97 éves korában elhunyt Ziza királyné tiszteletére. Habsburg Ottó rövid interjúban beszélt édesanyjáról - Maróthy László miniszter és a kormány lemondását is sürgették a nagymarosi beruházás színhelyén felvonulók - Terjed a Petőfi-kór, egyre több csoport kutatja Petőfi sírját Gazdaság: - "Magyarország gazdasági helyzete igen nehéz, de téved, aki válságosnak nevezi" -ez a véleménye a New York-i Kelet-Nyugat Gazdasági Intézet igazgatójának